A bacteriophage system for screening and study of biologically active polycyclic aromatic hydrocarbons and related compounds. - Hsu, W T (1977)
The usefulness of bacterial viruses for detecting substances that are potentially carcinogenic is reexamined as a model system for screening biologically active polycyclic aromatic hydrocarbons. A modification of the original assay procedure allows one to distinguish between aromatics that can modify the biological activity of infectious nucleic acids directly and those polycyclic aromatic hydrocarbons that require metabolic activation by Escherichia coli enzymes. The effect of chemical modification of several different polycyclic aromatic hydrocarbons, with respect to their biological activity in the phage assay system, is described. Among the 31 different compounds examined, (+/-)-anti-benzo[a]pyrene-7,8-diol-9,10-epoxide was the most potent inhibitor of infectious phage nucleic acid. The (+) and (-) isomers of the above racemic mixture did not differ significantly in their capacity to inhibit phage replication.